2017
DOI: 10.1007/s11695-017-2694-6
|View full text |Cite
|
Sign up to set email alerts
|

Experience with an Enhanced Recovery After Surgery (ERAS) Program for Bariatric Surgery: Comparison of MGB and LSG in 374 Patients

Abstract: The program was equally safe with both procedures. Postoperative antithrombotic heparin does not appear necessary in low-risk patients. Bariatric surgical ERAS programs are evolving and not yet standardized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 16 publications
1
24
0
Order By: Relevance
“…The complication rates in a fast-track bariatric surgery are modest: 2%–4% of all patients undergoing a bariatric procedure develops a major complication, such as staple line leakage or haemorrhage 13 14. Haemorrhage is not a frequently seen complication, but does have a substantial impact on the patient’s recovery.…”
Section: Discussionmentioning
confidence: 99%
“…The complication rates in a fast-track bariatric surgery are modest: 2%–4% of all patients undergoing a bariatric procedure develops a major complication, such as staple line leakage or haemorrhage 13 14. Haemorrhage is not a frequently seen complication, but does have a substantial impact on the patient’s recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were encouraged to be active agents of their own well-being instead of passive recipients of a surgical process. The detailed process of patients moving through the preoperative, operative, and postoperative ERAS protocol and follow-up, including the MGB and LSG procedures performed, and anesthesia and analgesia employed, has been described in detail in our original bariatric ERAS publication [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…During the 4-year development of our center’s bariatric ERAS protocol, we found that the use of thrombophylaxis selectively, only in morbidly obese postoperatively high-risk patients, was effective in ensuring safe outcomes while achieving more rapid mobilization [ 16 ]. The program’s evolution began in 2012 with a feasibility study of same-day discharge for patients undergoing laparoscopic adjustable gastric banding (LAGB).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations